PENGARUH PAJAK KENDARAAN BERMOTOR TARIF PROGRESIF DAN PENDAPATAN WAJIB PAJAK TERHADAP DAYA BELI KONSUMEN KENDARAAN BERMOTOR RODA EMPAT (Studi Empiris Di Kantor SAMSAT Kota Jayapura) - Waroi, Marice; Simanjuntak, Aaron M. A.; Andrianti, Hastutie Noor (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to determine the Effect of Progressive Vehicle Taxes and Taxpayer Income onÂ Consumer Purchasing Power. The research population is taxpayers who make motor vehicle taxÂ payments in the Jayapura City Samsat Office. The number of samples is 70 people. Determination ofÂ the study sample using the nonprobability sampling method, data was collected by distributingÂ questionnaires. The data analysis technique is multiple linear analysis. The results of the researchÂ conducted show that Progressive Vehicle Taxes have no significant positive effect on ConsumerÂ Purchasing Power, Taxpayer Income does not have a significant negative effect on ConsumerÂ Purchasing Power. The most dominant variable affects taxpayers regarding the tax on progressiveÂ tariff motor vehicles because they have a standard coefficient of beta 0 235.